Low breeding success and sharp population decline at the largest known Falkland skua colony - Catry, Paulo (2013)
The Falkland skua Stercorarius antarctica antarctica is a poorly known seabird. Demographic studies at the largest known colony of this taxon revealed a sharp population decline (47%) in just 5 years, between 2004 and 2009. The decline seems to be linked with a chronic low breeding success in the recent years and is consistent with a situation of virtually zero recruitment. The ultimate causes of the decline are, as of yet, unknown, but plausible explanations are examined and discussed. The reported population trends should be the cause of some concern, and more research and monitoring are desired.